Explicating the multifunctional roles of tocotrienol and squalene in promoting skin health - Nevvin Raaj Morgan; Kasthuri Bai Magalingam; Ammu Kutty Radhakrishnan; Mohan Arumugam; Adawiyah Jamil; Saatheeyavaane Bhuvanendran (Wiley, 2024)
Abstract The skin is the largest organ in the integumentary system, protecting against various external threats, including ultraviolet exposure, heat, infections, dehydration and mechanical injuries. Skin disorders can arise from various causes, including allergic reactions or breaches in the skin barrier, which allow microorganisms or chemicals to penetrate the sweat ducts. These conditions encompass a wide range of issues, including acne, xerosis (dry skin), fungal infections, atopic dermatitis (eczema) and psoriasis. Collectively, these ailments affect a significant portion of the global population, impacting approximately one‐third of people worldwide. Additionally, oxidative stress induced by ageing and prolonged exposure to ultraviolet rays can manifest in visible alterations such as pigmentation, wrinkling and dehydration. Recent investigations have underscored the potential of natural antioxidant compounds in safeguarding skin health and combating ageing‐related changes. Tocotrienols, a subgroup of vitamin E, have garnered significant attention owing to their antioxidant and anti‐inflammatory properties. Significant amounts of tocotrienols can be found in rice bran, olive, oats and hazelnuts. Similarly, squalene, predominantly sourced from fish liver oils such as those from sharks, has been used as an emollient in cosmetic formulations. This article offers a comprehensive review of existing literature elucidating the dermatological benefits associated with tocotrienols and squalene, emphasising their roles as antioxidants, anti‐inflammatories, skin barrier protection and facilitators of wound healing. Moreover, it sheds light on contemporary research findings suggesting these compounds' therapeutic promise in managing and ameliorating various skin conditions.